RESISTANCE OF Solanum phureja TO Myzus persicae: MEDOTOLOGY AND CRITERIA - R. DE SANABRIA, GILMA LEONOR; MOSQUERA-PARIS, FELIPE (Revista Colombiana de Entomología, 1978)
The possible presence of resistance in 65 cultivars of Solanum phureja (Juz et Buk) to the aphid Myzus persicae (Sulzer) (Homoptera: Aphididae), the insect vector of several viruses in potatoes was evaluated under laboratory conditions at the ICA Experimental Center "Tibaitatá", Mosquera, Cundinamarca. The excised leaves method with artificial infestation was used to rear the aphids. In the evaluation, the maximum number of aphids in each cultivar was considered as an indicator of fecundity and the percentage of alates as a measure of the adaptability of the aphids to the cultivar. There were no cultivars immune to the aphids, 16 cultivars in which the maximum population was less than 195.75 aphids were considered resistant due to adverse effects on the fecundity of M. persicae. Of these 16 cultivars, seven were considered as good sources of resistance against the "potato leafroll virus" (PLRV), due to the fact that the percentage of alates was high; the other was considered as a good source of resistance to stylet-borne viruses. In general, it was observed that there was a good association between the number of aphids on the underside of the leaves and the number of hairs, is the maximum number of aphids present in cultivars with a higher number of hairs. It is possible that this characteristic may be used in the preliminary identification of resistant cultivars. The results of the laboratory test indicated that the procedures followed in these studies can be used in the future evaluations for the identification of cultivars resistant to M. persicae